2016
DOI: 10.1111/nph.13930
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome duplication in coast redwood (Sequoia sempervirens) and its implications for explaining the rarity of polyploidy in conifers

Abstract: SummaryPolyploidy is common and an important evolutionary factor in most land plant lineages, but it is rare in gymnosperms. Coast redwood (Sequoia sempervirens) is one of just two polyploid conifer species and the only hexaploid. Evidence from fossil guard cell size suggests that polyploidy in Sequoia dates to the Eocene. Numerous hypotheses about the mechanism of polyploidy and parental genome donors have been proposed, based primarily on morphological and cytological data, but it remains unclear how Sequoia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 65 publications
3
60
0
Order By: Relevance
“…Our evidence supports two WGDs in ginkgo, with an ancient WGD occurring 515 to 735 mya, consistent with previous reports [46–48, 60, 61], and a more recent event reported for the first time in this study and not yet observed in other seed plants [46]. This recent WGD may have uniquely contributed to the morphological and biological diversity of the gingko lineage.…”
Section: Discussionsupporting
confidence: 91%
“…Our evidence supports two WGDs in ginkgo, with an ancient WGD occurring 515 to 735 mya, consistent with previous reports [46–48, 60, 61], and a more recent event reported for the first time in this study and not yet observed in other seed plants [46]. This recent WGD may have uniquely contributed to the morphological and biological diversity of the gingko lineage.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Adansonia digitata is a recent tetraploid (Baum and Oginuma ), but no recent peak is observed. One possibility is that this was an autotetraploidy event that occurred recently enough that tetrasomic inheritance is still in effect, which could prevent paralogs diverging enough to result in two separate gene models during transcriptome assembly (Scott et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the absence of biased fractionation should not be considered informative when attempting to differentiate ancient allopolyploidy from ancient autopolyploidy. Autopolyploidy has also been inferred through coalescent modeling in Capsella bursa‐pastoris (St. Onge et al, ) and through phylogenetic analysis of orthologous transcripts in the conifer Sequoia sempervirens (Scott et al, ). Unfortunately, extensive genomic rearrangements after WGD, as well as more recent WGDs, can obscure the nature of an ancient WGD to a point where multiple lines of evidence either cannot resolve an auto‐ or allopolyploid origin or produce conflicting results (e.g., Chaintreuil et al, ).…”
Section: Ancient Autopolyploidymentioning
confidence: 99%